Waning immunity to SARS-CoV-2 following vaccination or infection - Hernandez-Suarez, Carlos; Murillo-Zamora, Efrèn (Frontiers in Medicine, 2022)
We use survival analysis to analyze the decay in the protection induced by eight SARS-CoV-2 vaccines using data from 33,418 fully anonymized patients from the IMSS public health system in Mexico, including only previously vaccinated, confirmed SARS-CoV-2 positive with a PCR test. We analyze the waning effect in those with complete vs. incomplete dose fitting a Weibull distribution. We compare these results with an estimate of the waning effect due to active infection. In two-dose vaccines, we found that the average protection time of a complete dose increases 2.6 times compared to that of an incomplete dose. All analyzed vaccines provided a protection that lasted longer than the protection due to active infection, except in those patients that did not fulfilled the complete dose. The average protection of a full dose is 2.2 times larger than that provided by active infection. The average protection of active infection is about the same as the average protection of an incomplete dose. All evaluated vaccines had lost most of their protective effect between 8 and 11 months of application of first shot. Our results highly correlate with NT50 and other estimates of vaccine efficacy. We found that on average, vaccination increases Age50, the age at which there is a 50% probability of severe disease if infected, in 15 years. We also found that Age50 increases with mean protection time.